Reassessment of Masinloc and Oyon Bay protected landscape and seascape management effectiveness - Pag-ong, Anthony Ian G.; Nisperos, Dulce Marie P. (2024)
The Masinloc and Oyon Bay Protected Area Landscape and Seascape (MOBPLS) management effectiveness was re-assessed using the instruments’ Management Effectiveness Assessment Tool (MEAT) and Management Effectiveness Tracking Tool (METT). The first time it was assessed in 2013, it failed in both instruments. The study's respondents comprised the Protected Area Management Bureau (PAMB) members, Protected Area Management Office staff, municipal local government units, fisherfolk organizations, and residents along MOBPLS with livelihoods in the area. Thirty (30) respondents each answered the MEAT and METT, respectively. The result from the MEAT instrument shows that MOBPLS is effectively managed based on the cumulative score of 81.07, which just about falls in the range of Level 4, which translates to MPA being effectively institutionalized.
Four out of nine management focus criteria received a 100% score from the respondents —namely management plan, legal instrument, community participation, and site development. METT results came from the threats that challenge the management of MPA and the management effectiveness score itself. Human intrusion and disturbance, together with transportation and service corridors, had the highest score for acting as a challenge for MOBPLS management. Human intrusion and disturbance are depicted mostly by fish pens being set up in an area more than its allowed range.
The METT effectiveness percentage score was 86.59%, higher than the 37% mark from the initial 2013 benchmarking. The ten-year (2022–2032) MOBPLS Management Plan developed that involved stakeholders and the formation of a technical working group that made and offered consultations, meetings, workshops, and focus group discussions could have helped in this turnout. All PAMB meetings reveal robust attendance by the MOBPLS stakeholders, which shows dedication to the execution of the mandate of what a marine protected area is, and these endeavors – if maintained – could potentially steer toward a continuous and sustainable management effectiveness.
Keywords: Landscape ecology; Sustainable development and the environment